SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI PENERIMAAN PEGAWAI BARU MENGGUNAKAN METODE KNN DAN WEIGHTED PRODUCT - Febriani, Siska (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
Searching for prospective employees is quite an important thing in the company because every job done by employees will affect the stability of the company. In the recruitment of employees, the quality of prospective applicants is already convincing, but the salary he submits is not in accordance with the ability of the company, or the prospective applicants do not match the criteria that the company is looking for. This mismatch will certainly slow down the company to find the best staff. The results of this study are to provide recommendations for the best employees who understand some of the criteria set by the system using the k-nearest neighbor (KNN) method and weighted product (WP). The parameters used to obtain wisdom are using GPA values, academic values, science and technology values and interview scores. The data that will appear at the conclusion is the ranking of the participants, the type of classification and recommendations chosen by the company. With these data, the company can determine the next policy that can be taken. The results of the accuracy obtained are 87% with a value of k = 3.